2017
DOI: 10.1002/macp.201700010
|View full text |Cite
|
Sign up to set email alerts
|

A New Four‐Arm Organosiloxane with Thermopolymerizable Trifluorovinyl ether Groups: Synthesis and Conversion to the Polymer with both Low Dielectric Constant and Low Water Uptake

Abstract: A new fluoro‐containing four‐arm organosiloxane has been successfully synthesized, which can be easily converted to a cross‐linked network, showing water uptake of below 0.12 wt% (maintained in boiling water for 72 h) and dielectric constant of below 2.56 with dissipation factor of near 1.8 × 10−3 at 30 MHz, as well as showing high transparency and good thermostability. These data indicate that this new organosiloxane is suitable as an adhesive or sealant for the applications in microelectronic industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…In order to confirm the degree of the cyclization reaction, the cured silicone resins were retested by DSC. As shown in Figure 4 b, the exothermic peaks on DSC curves disappeared [ 25 , 28 ], which indicated that the cyclization reaction of the TFVE groups was complete.…”
Section: Resultsmentioning
confidence: 99%
“…In order to confirm the degree of the cyclization reaction, the cured silicone resins were retested by DSC. As shown in Figure 4 b, the exothermic peaks on DSC curves disappeared [ 25 , 28 ], which indicated that the cyclization reaction of the TFVE groups was complete.…”
Section: Resultsmentioning
confidence: 99%
“…synthesized a series of multifunctional‐TFVE‐based organsiloxane monomers through different methods (Figure 3.2). [ 15,17,66‐67 ] The PFCB‐based polysiloxanes displayed good thermostability and low D k (Table 3.2). X‐TFVE was synthesized through hydrolysis of a TFVE‐containing siloxane followed by the hydrosilylation reaction.…”
Section: Organosilicon Polymers For Low‐k Materials Applicationmentioning
confidence: 99%
“…PFCB polymers are mainly prepared by the [2π + 2π] thermocyclization of trifluoroethylene aryl ether (TFVE) monomer . Recently, PFCB polymers have attracted extensive attention of researchers in various fields including electronics industry, aerospace, fuel cells, optical waveguide materials, and coatings because of the unique properties such as low dielectric property, low hygroscopicity, high thermal stability, chemical solvent resistance, and low birefringence. However, most of the research interests are focused on the functionality of PFCB group.…”
Section: Introductionmentioning
confidence: 99%